2022
DOI: 10.1128/spectrum.01548-22
|View full text |Cite
|
Sign up to set email alerts
|

Pf4 Phage Variant Infection Reduces Virulence-Associated Traits in Pseudomonas aeruginosa

Abstract: Filamentous bacteriophages can become superinfective and infect P. aeruginosa , even though they are inserted in the genome as lysogens. Despite this productive infection, growth of the host is only mildly affected, allowing the study of the interaction between the phage and the host, which is not possible in the case of lytic phages killing rapidly their host.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 128 publications
3
16
0
Order By: Relevance
“…Pertinent to our study, a recent report by Tortuel et al showed that P. aeruginosa infected with SI-Pf phage had reduced virulence in lettuce plant and Caenorhabditis elegans infection models (21). Tortuel et al reported decreased spread of the SI-Pf within the lettuce leaf, as well as a reduced rate of C. elegans mortality when compared to control, respectively.…”
Section: Introductionsupporting
confidence: 83%
See 3 more Smart Citations
“…Pertinent to our study, a recent report by Tortuel et al showed that P. aeruginosa infected with SI-Pf phage had reduced virulence in lettuce plant and Caenorhabditis elegans infection models (21). Tortuel et al reported decreased spread of the SI-Pf within the lettuce leaf, as well as a reduced rate of C. elegans mortality when compared to control, respectively.…”
Section: Introductionsupporting
confidence: 83%
“…Importantly, the specific mutations in the Pf chromosome that result in a super-infective phage were not well delineated. While some studies have detected mutations in the phage repressor and in the intergenic region between the repressor and the exsicionase gene, other have reported mutations in other phage genes such as PA0723, PA0724 and PA0725 (21). None of these had been experimentally validated as being at cause.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…F I G U R E 2 Pf4 replication downregulates P. aeruginosa quorum sensing and phenazine biosynthesis genes. RNAseq was performed on P. aeruginosa PAO1 infected with Pf4 compared to uninfected cultures in LB broth as described in reference (Tortuel et al, 2022). To confirm the results from the BATCH assay, we expressed Histagged PqsA and S-tagged PfsE in E. coli and purified His-tagged protein complexes by affinity chromatography (Figure 4e).…”
Section: The Pf4 Phage Protein Pfse Binds To Pqsamentioning
confidence: 99%